Estudo multicasos sobre design de produtos na área de tecnologia assistiva - Soares, Juliana Maria Moreira (2015)
This research was intended to contribute about the understanding of the product development process (PDP) of Assistive Technology (AT), by using a multicases study methodology. The considerations present in this work were made possible through the selection of four case studies , consisting of Assistive Technology brazilian developers, focused on products to the public with physical-motor disabilities. The first case is located in a university center, consisting in a development of a triangular walker for children and teenagers with disabilities (mostly elapsed from cerebral palsy), and it was conducted by a team composed of undergraduates and graduate students, and researchers, at a university in the state of São Paulo (SP ? Brazil). Beside this case is another AT project, which was initiated within doctoral research, conducted by another university of the state of São Paulo, which is in an automated mobility device for wheelchairs. The third case is characterized as a private industry, located in the north-central state of São Paulo, which develops and produces various assistive products for people with multiple types of physical disabilities. The latter approach was made up as an organization of the third sector inserted in TA market, which is a developer of assistive securities, located in Belo Horizonte, capital of Minas Gerais state, Brazil. Understanding the development process of AT product consisted in a primary object of this research, while capture the vision of assistive technology developers about collaboration issues and relations situated in the subjective field of user-product consisted on secondary objectives of this dissertation. This way, the possible influence of collaborative and emotional design in Assistive Technology development processes were then issues discussed by this research, with the intention to outline the perspectives of such approaches in the PDP of assistive product field, in addition to begin the discussion about the need of studies on the issue of product development in this area.